Analisis Gerakan Stasiun Pemantauan Patahan Opak - Widjajanti, Nurrohmat (2016)
This paper presents the results of Opak Fault geodynamic study in geometric aspect. Previous research has been carried out optimization of Opak Fault monitoring network. After having optimum network then monitoring points (TGD, OPK and SGY) built permanently in optimized locations. Furthermore, the monitoring points measured by GNSS survey with relatively static method in 2013 and 2014. GNSS measurements at monitoring points conducted again in 2015. The result is a three-dimensional coordinates of the points TGD, OPK and SGY at the region of Opak Fault in 2015. Furthermore, the three-dimensional coordinates were analyzed movements compared to the coordinates of previous studies in 2013 and 2014. The results showed that the velocity value of monitoring point’s movement from 2014 to 2015 reached fraction of centimeter. The velocity of East component is relatively larger than North components. The horizontal movement of the monitoring points mostly toward the Southeast.